VALUE-ADDED ANALYSIS OF TEMPE PRODUCTION FROM SOYBEANS IN GUNTUNG PAIKAT, SOUTH BANJARBARU - Defina Rozita Putri; Ana Zuraida; Suslinawati Suslinawati (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
This study analyzes the value addition of soybean processing into tempe in Guntung Paikat, South Banjarbaru District, Banjarbaru City, using a case study of Mr. Suparji’s enterprise. The objective of the research was to determine output value, input value, labor utilization (measured in workdays), and to identify challenges encountered in tempe production related to value addition. A quantitative method with a case study approach was employed, conducted from March to June 2025, involving two respondents: the owner and his son as a worker. Data were analyzed descriptively, and value addition was calculated using the Hayami method. Results show that tempe production was carried out through simple processes including sorting, washing, soaking, peeling, boiling, inoculation with yeast, wrapping, and fermentation. The value addition, defined as the difference between output value, other input contributions, and input costs, was IDR 20,133 per kilogram, with a ratio of 71.90%. This high ratio indicates strong economic feasibility, as it exceeds the 40% threshold.